2018
DOI: 10.1093/hmg/ddy343
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate induces autophagy and improves hepatic lipid metabolism in glycogen storage disease type Ia

Abstract: Glucose-6-phosphatase α (G6Pase) deficiency, also known as von Gierke’s Disease or Glycogen storage disease type Ia (GSD Ia), is characterized by decreased ability of the liver to convert glucose-6-phosphate to glucose leading to glycogen accumulation and hepatosteatosis. Long-term complications of GSD Ia include hepatic adenomas and carcinomas, in association with the suppression of autophagy in the liver. The G6pc−/− mouse and canine models for GSD Ia were treated with the pan-peroxisomal proliferator-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
4
30
0
Order By: Relevance
“…A rational therapeutic approach for the treatment of NAFLD is to increase hepatic energy expenditure and thereby increase hepatic fat oxidation. Recently, we showed that the use of PPAR-α agonists, in particular fenofibrate, prevented NAFLD and hepatic injuries in GSDI, as previously described in diabetes [66][67][68]. Interestingly, the activation of β-oxidation by fenofibrate promoted the utilization of G6P through lipid metabolism, avoiding the accumulation of glycogen [66].…”
Section: Imbalance Of Glucose-6 Phosphate Metabolism Leads To Metabolsupporting
confidence: 53%
“…A rational therapeutic approach for the treatment of NAFLD is to increase hepatic energy expenditure and thereby increase hepatic fat oxidation. Recently, we showed that the use of PPAR-α agonists, in particular fenofibrate, prevented NAFLD and hepatic injuries in GSDI, as previously described in diabetes [66][67][68]. Interestingly, the activation of β-oxidation by fenofibrate promoted the utilization of G6P through lipid metabolism, avoiding the accumulation of glycogen [66].…”
Section: Imbalance Of Glucose-6 Phosphate Metabolism Leads To Metabolsupporting
confidence: 53%
“…For the vast majority of patients, the treatment is limited to treating the symptoms, rather than curing the disease. Still, the administration of small molecules could improve some mitochondrial parameters, and possibly alleviate mitochondrial disease symptoms [28][29][30][31][32]42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with previously reports by others including us, showing Bezafibrate to be beneficial for certain mitochondrial diseases. This could possibly be attributed to increased ability to utilize fatty acids [29,31,32,34,41] Furthermore, Bezafibrate had a positive effect on mitochondrial morphology, leading to decreased mitochondrial elongated phenotype, which was approaching controls (higher levels of solitary mitochondria, and lower levels of elongated ones). This might indicate that…”
Section: Discussionmentioning
confidence: 95%